Neue zoophage Gallmücken-Gattungen (Diptera: Itonididae). - Möhn, Edwin (Contributions to Entomology = Beiträge zur Entomologie, 1955)
Nomenclatural Acts vasta Möhn, 1955 (Chiliodiplosis), spec. n. Chiliodiplosis Möhn, 1955 (Itonididae), gen. n. Phonodiplosis Möhn, 1955 (Itonididae), gen. n. casta Möhn, 1955 (Phonodiplosis), spec. n.